‘Confusion of horizons’ with unwanted Others: Frustrations, results and effects of ethnographic practices in the realm of justice and public safety. - Leonardo Brama; Roberto Kant de Lima; Fabio Reis Mota (Vibrant: Virtual Brazilian Anthropology)
Abstract: By reviewing various ethnographic experiences, we examine how inhospitality, unwanted and incongruous relationships, tensions and conflicts, inform a type of fieldwork and nevertheless allow-despite the ‘anti-manualistic’ form of this work-creating opportunities for understanding and interpreting the schemes, practices and worldviews of the subjects studied. Despite confronting tortuous paths, mediated by a ‘confusion of horizons’, anthropological research, when informed by questions and analyses with a good theoretical organization and conducted according to qualified ethnographic education, allows deducing broader aspects, related to the practices and representations of the world not only of the universe studied, but of its surroundings. By presenting the results of ethnographies and interactions with various actors in the fields of justice and public safety, we present some analytical devices developed in these two fields through different ethnographic experiences, such as the ‘inquisitorial tradition’ and ‘schismatic rationality’.